whisky jack (1970)
whisky jack This "whisky-Jack" or "whisky-Johnnie", the Indians _ouicheat-chan_, is ofen the only feathered creature one can discover in the thick forest.This 'Canadian jay' is supposed by the natives to have something of an evil spirit in it, it is said to inform the various animals of the approach of Indians. Therefore they rarely fail to kill the jay wherever found. The Whisky-Jack was never permitted to enter the Indian lodge, writes Le Jeune (491), in 1633. But / the gizzard of this bird was formerly examined with the greatest care to see if it contained any fragments resembling the bones of a large animal. believing that if such were discovered, they would soon kill one of the same kind. PRINTED ITEM W.J. KIRWIN SEP 1970 JH SEP 1970 Not used Not used Withdrawn withdrawn but no stamp